Electropolishing of Additively Manufactured Ti-6Al-4V Surfaces in Nontoxic Electrolyte Solution - G. M. Tsoeunyane; N. Mathe; L. Tshabalala; M. E. Makhatha (Advances in Materials Science and Engineering)
The reduction of surface roughness on additively manufactured components has become a critical factor in engineering applications. This paper reports the electropolishing of additively manufactured Ti-6Al-4V by powder bed selective laser melting (SLM) using a nontoxic electrolyte solution. The results have shown that the salt-based electrolyte can be used to electropolish titanium alloys. The surface waviness of the as-built Ti-6Al-4V alloy was reduced by five times the average roughness of the as-built specimen. The minimum surface roughness obtained was 9.52 μm. The specimens were characterized by scanning electron microscope, Gwyddion software, and electrochemical impedance spectroscopy (EIS) to evaluate the surface morphology, surface profile, and charge transfer resistance. The X-ray photon spectroscopy (XPS) and X-ray diffraction (XRD) spectroscopy were used to characterize the surface chemistry of the specimen. The XPS and XRD showed TiO2 as the significant component on the surface of Ti-6Al-4V, and the atomic percentage on the surface increased after electropolishing. In addition, the EIS data indicated the high charge transfer resistance of the electropolished specimen, which shows the growth formation of the oxide layer.